Influence of microwave-assisted oxidant stimulation on pore structure and fractal characteristics of bituminous coal based on low-temperature nitrogen adsorption. (1st November 2022) - Xu, Chaoping; Li, He; Lu, Yi; Liu, Ting; Lu, Jiexin; Shi, Shiliang; Ye, Qing; Jia, Zhenzhen; Wang, Zheng
Highlights: The pore structure evolution of coal before and after stimulation was investigated. Oxidation simplifies pore structure while microwave heating destroys pore space. Microwave-assisted oxidation promotes the dilatation and connection of pores. The pore volume of bituminous coal increases by 31.94% after stimulation. Abstract: Coal reservoir stimulation is a process of enhancing coalbed methane (CBM) production by dilating, opening, and extending the width, length, and connectivity of the natural pore/fracture systems. Novel stimulation techniques including N2 injection, ultrasonic wave, acidification, and plasma treatment have been proposed, but none is ubiquitously successful. As an alternative stimulation method, oxidation dissolves the organic molecules that plug the pores and fractures resulting in opening and interconnecting passageways to flow gas through the reservoir. However, oxidation has minimal effect on pores and microfractures. Microwave-assisted oxidation may be a potential stimulation strategy. In this study, the influence of microwave-assisted oxidation on pore structure and fractal characteristics of bituminous coal was investigated based on low-temperature nitrogen adsorption. Results show that microwave-irradiated coal has the highest fractal dimension D 2, implying that microwave heating destroys the pore structure. The microwave-induced fractures are blocked by coal particles and mineral debris. The reduction in the micropore volume, specific surface area, and D 2 of oxidized coal confirms that oxidation simplifies the pore structure. Combined with microwave heating, the oxidizer easily penetrates into the coal matrix. As a result, the total pore volume increases by 31.94% and the isolated pores are connected. This study fills a knowledge gap on microwave-assisted oxidation stimulation and contributes to the decision of selecting appropriate method to enhance the exploitation of CBM.